The marketing firm and consumer choice: implications of bilateral contingency for levels of analysis in organizational neuroscience - Foxall, Gordon R. (Frontiers in Human Neuroscience, 2014)
The emergence of a conception of the marketing firm (Foxall, 1999a) conceived within behavioral psychology and based on a corresponding model of consumer choice, (Foxall, 1990/2004) permits an assessment of the levels of behavioral and organizational analysis amenable to neuroscientific examination. This paper explores the ways in which the bilateral contingencies that link the marketing firm with its consumerate allow appropriate levels of organizational neuroscientific analysis to be specified. Having described the concept of the marketing firm and the model of consumer behavior on which it is based, the paper analyzes bilateral contingencies at the levels of (i) market exchange, (ii) emotional reward, and (iii) neuroeconomics. Market exchange emerges as a level of analysis that lends itself predominantly to the explanation of firm—consumerate interactions in terms of the super-personal level of reinforcing and punishing contingencies: the marketing firm can be treated as a contextual or operant system in its own right. However, the emotional reward and neuroeconomic levels of analysis should be confined to the personal level of analysis represented by individual managers on the one hand and individual consumers on the other. This also entails a level of abstraction but it is one that can be satisfactorily handled in terms of the concept of bilateral contingency.